PENGEMBANGAN LKPD BERBASIS READING, MIND MAPPING, AND SHARING PADA MATERI SENYAWA HIDROKARBON UNTUK KELAS XI SMA/MA - muhammad hafiz al ridha (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2020)
Abstract This Research aims to develop Student Worksheets Based on RMS on the Hydrocarbon Compound valid based on the feasibility aspect of content, characteristics of RMS, language, serve and graphic. The type of this research is research and development (R and D) with reference to the development process of Plomp. The subject of this research is student worksheets based on RMS. Instrument of data collection are validation given to three validators, and from analysis data obtained by the validity of aspect of content, aspect of characteristics of RMS, aspect of language, aspect of serve, and aspect of graphic are 93.9%, 95%, 96.8%, 100% and 92% with valid category. Student  worksheets which validated by the validators tested to 32 students and get response result with percentage of 91.3% with very good criteria, and from two teachers get response result with percentage of 97% with very good criteria. Based on the result of data analysis can be concluded that student worksheets based on RMS that produced is valid and can be used for the Hydrocarbon Compound.                                                                                                           Key words: Hydrocarbon Compound, Student Worksheet, RMS